2022
DOI: 10.1007/s10531-022-02377-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive genetic sampling is one of our most powerful and ethical tools for threatened species population monitoring: a reply to Lavery et al.

Abstract: Noninvasive genetic sampling (genetic tagging) of individuals is one of the most powerful and ethical tools for threatened species population monitoring. A recent review of the threats to Australia’s rock-wallabies (Petrogale spp.) and the methods for their monitoring stated that noninvasive genetic sampling (faecal DNA analysis) is not viable for estimating population size and trends for species in this genus. We feel that it is important to respond as such statements have the potential to stifle the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Identifying DNA collection methods that minimize mortality and disruption to organisms is important when the taxa being studied are rare or are of high conservation priority [6][7][8][9][10]. Our results demonstrated that both swabbing and tissue biopsy collection…”
Section: Discussionmentioning
confidence: 78%
“…Identifying DNA collection methods that minimize mortality and disruption to organisms is important when the taxa being studied are rare or are of high conservation priority [6][7][8][9][10]. Our results demonstrated that both swabbing and tissue biopsy collection…”
Section: Discussionmentioning
confidence: 78%
“…A noninvasive approach to monitor populations of scarce species such as the black‐footed cat, could be more sustainable and reliable (Banks & Piggott, 2022 ; Piggott et al., 2008 ). DNA extracted from scats reduces the need to handle the animal (Ramon‐Laca et al., 2015 ) and could provide information on individual occupancy (Fernando et al., 2003 ), paternity and kinship (Constable et al., 2001 ; Wang et al., 2015 ), genetic diversity (Mengulluoglu et al., 2019 ), species identification and sex (Dalén et al., 2004 ; Kurose et al., 2005 ), identifying hybrids (Adams et al., 2003 ), and estimating population sizes (Banks et al., 2002 ; Eggert et al., 2003 ; Piggott et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA sampling methods, however, are not infallible, and there is one major limitation that must be assessed via pilot studies for each new study species prior to using the method as a monitoring tool (Banks and Piggott 2022). DNA recovered from scats is often of low quantity and quality (Carpenter and Dziminski 2017), resulting in a high risk of genotyping errors (allelic dropout and false alleles) (Piggott and Taylor 2003 a ).…”
Section: Introductionmentioning
confidence: 99%